Review of the Adequacy of and Options for Supplementing Fund Resources. (Policy Papers; Policy Paper ;, 2009)
This review discusses the potential scale of a possible increase, as well as modalities that would facilitate a prompt increase in the Fund's resources should the need for additional resources be agreed. While a permanent increase in Fund resources has traditionally been achieved through an increase in quotas, borrowing has often been used to bridge to a general quota increase given the substantial time involved in the latter undertaking. At a time of crisis, the case for such an approach is even stronger. The precise design and scope of any such borrowing would need to be considered in consultation with potential creditors, and with careful attention to the broader implications for the Fund's finances.